199k views
4 votes
Solve the system by substitution y=6x and 7x-8y=-41

User Tom Fuller
by
4.5k points

2 Answers

6 votes
7x - 8y = -41
7x - 8(6x) = -41
7x - 48x = -41
-41x = -41
x = 1
User Fpopic
by
5.5k points
2 votes

Answer:

x = 1

y = 6

Explanation:

y = 6x --------------(I)

7x - 8y = -41 ------------(II)

Substitute y =6x in equation (II)

7x - 8*(6x) = -41

7x - 48x = -41 {Combine like terms}

-41x = -41

x = -41/-41

x = 1

Plug in x = 1 in equation (I)

y = 6*1

y = 6

User Tomasz Myrta
by
4.1k points